Rehydration of dry corn preserves the desirable bacterial community during ensiling. Issue 17 (25th August 2020) - Carvalho-Estrada, Paula de Almeida; de Andrade, Pedro Avelino Maia; Paziani, Solidete de Fátima; Nussio, Luiz Gustavo; Quecine, Maria Carolina
ABSTRACT: This study evaluated the rehydration approach of mature corn grains as an alternative for high-moisture corn grain silage production in distinct corn hybrids, storage period, cultivation locations and kernel maturity at plant harvest. High-moisture corn was used as a control. The dry matter content and pH of the silage were measured, and the bacterial community associated with corn grains pre- and post-ensiling was also assessed through 16S rRNA high-throughput sequencing. The decrease in pH value was directly linked to an ecological microbial succession of Enterobacteriales and Actinomycetales to Lactobacillales in the silage at 120 days after storage, either in rehydrated or high-moisture corn. These results were similar for both maize production locations and hybrids tested. Finally, the similarity between the ensiling processes including rehydrated corn and the high-moisture corn grain silages proves the reliability of the rehydration approach as an alternative for the maintenance of a successful bacterial community structure and composition capable of producing high-quality silages from dent and flint corn hybrids in tropical conditions. Abstract : The hydration approach as a reliable alternative for the maintenance of the bacterial community structure and composition of silage of dent and flint corn from tropical environments.